Analisis Kesalahan Berbahasa Indonesia Dalam Percakapan Grup Whatsapp Mahasiswa Pendidikan Bahasa Indonesia Reguler E 2020 - Wiwit Wanrah Nasution; Putri Evani Malau; Jihan Aqilah Zahra; Heni Atikah; Frinawaty Lestarina Barus; Emasta Evayanti Simanjuntak (Universitas Maritim AMNI Semarang, 2023)
In this study, the data that will be used as research objects are Regular Indonesian Language Education Students E 2020. This study aims to find out Indonesian language errors in WhatsApp group conversations for regular students E 2020. The method used in this research is a qualitative descriptive method. The data collection technique comes from screenshots of text from the WhatsApp group application for Indonesian Language and Literature Education Regular E 2020. The research method contains an explanation of the methods used by researchers in conducting research. In this section the researcher explains the scientific procedures carried out by the researcher to produce a conclusion. The method contains research approaches and methods, data sources/populations and samples, methods for selecting samples/determining data sources, instruments, data collection methods, and data analysis techniques. This section contains a description of the procedure and research steps according to the topic being studied. The results of this study are that there are many mistakes made by students in communicating in groups such as using incorrect spelling, using non-standard words and using forgotten punctuation marks.